LOCAL WISDOM AS THE SOURCE OF THE NEW ECONOMY: A CASE STUDY OF DANGEAN, GEDANGAN VILLAGE, BOYOLALI REGENCY - Bayu Grendo Sigarete; Varid Adi Kurniawan; Muhammad Atok Ilah (UPT Penerbitan Universitas Jember)
Social bonds within communities form a culture which is reflected in daily life in the form of custom and tradition. Cultures that form a local wisdom shows characteristics typical of a society which is the tourism perspective, the local wisdom became one source of attractiveness that can be rose and developed as one of the attractions in the tourism activities. This research uses qualitative descriptive method. The research occurred in the territory of the Dangean, Boyolali Regency. The collecting data is done by structured interviews with the respondents as many as 17. Ambarrukmo Tourism Institute (STIPRAM) researchers found the people of Dangean has a strong social bonds that manifested in the philosophy of the village name, the society’s economic activities such as farming and ranching, the traditions which is continuously implemented by the people in the form of community service, mutual cooperative, “memetri” (anniversary of the village), and ”Nyadran” (as alms to the earth), also the Javanese tradition sustainably maintained by society as the wedding procession. The existences of local wisdom are still strong in the society of Dagean, it have potentially to raised and developed as a rural economic activities through the concept of Rural Tourism.